Kepastian Hukum Persyaratan Evaluasi Kualifikasi Sisa Kemampuan Paket Untuk Usaha Non Kecil Pada Dokumen Pemilihan Tender Pekerjaan Konstruksi - Raharjo, Dandy Ilham; Yuslim, Yuslim; Mannas, Yussy Adelina (Nagari Law Review, 2024)
This research aims to analyze the legal certainty of the qualification evaluation requirements for the remaining capability packages for non-small businesses for tenders for construction work carried out by the Procurement Committee. The tender has 4 (four) requirements that must be met, namely administrative, qualification, technical and price requirements. One of the qualification requirements that must be fulfilled Provider is the remaining capacity of the non-small business package. The remaining package capacity is the maximum limit on the amount of work that may be carried out by the construction work provider at the same time as the procurement contract is signed. Normative research is understood as research to test applicable norms or provisions. Research results: SKP qualification evaluation requirements for non-small businesses have 2 (two) provisions for non-small businesses, the Package Capability (KP) value is determined as 6 (six) or 1.2 (one point two) N, Providers who have more experience from 6 (six) after this regulation is promulgated and submits a list of jobs that have been handled simultaneously in the last 5 (five) years, the results of the evaluation of being able to handle packages simultaneously will increase, for example 1.2 (one point two) x 6 ( six) becomes 7.2 (seven point two). However, in terms of determining the results of decimal numbers, there are no more detailed and strict provisions for rounding up or down for decimal numbers. Legal certainty seen from the opinion of Gustav Radbruch stated that legal certainty is achieved if it fulfills 4 (four elements), one of which is that the facts contained in the law must be formulated in a clear way, then the requirements for evaluating the remaining capabilities of non-small business packages which have not been regulated are related to provisions 1.2 ( one point two)N has not been fulfilled.